Estabilidade de Standing waves - Santos, Alisson Darós (2014)
This work is concerned with the orbital stability of special solutions called "standing waves" for Hamiltonian systems in a real and invariant Hilbert space under the action of a specific group of isometries in such space. The stability investigated is orbital in the usual sense for a dynamical system and is with respect to perturbations of the initial condition. Initially we approach the problem in an abstract manner and then we show an application of the discussed method.